A standardized antenatal class reduces the rate of cesarean section in southern Italy: A retrospective cohort study. Issue 16 (April 2018) - Cantone, Daniela; Lombardi, Annamaria; Assunto, Debora Antonia; Piccolo, Michela; Rizzo, Natascia; Pelullo, Concetta Paola; Attena, Francesco
Abstract : Abstract: Italy, along with Poland and Hungary, has the highest cesarean section rate (35.7%) in Europe. Among Italian regions, Campania has the highest rate of cesarean section (58.4%). We developed a standardized antenatal class to evaluate whether women who attend this class during pregnancy have a lower cesarean section rate. This antenatal class was developed according to the indication of the Italian Ministry of Health and the World Health Organization. We selected a cohort of women who participated in this antenatal class and a cohort of women who did not participate. We collected information on the mode of delivery, and other characteristics, of these women from certificate of birth assistance form available in 2 hospitals where the women gave birth. Among women who participated in the antenatal class, there were more Italians, the women were more educated, more women were employed and there were more primiparas compared with those who did not participate. Non-participants of antenatal class showed a higher rate of cesarean section than those who participated (56.2% vs 23.1%; relative risk [RR] = 2.43; 95% confidence interval [CI] 1.95–3.03; P < .0001), as well as after adjustment for other variables. This difference was stronger in 1 hospital (RR = 2.88; 95% CI 2.13–3.89; P < .0001) than in the other hospital (RR = 1.86; 95% CI 1.36–2.55; P < .0001). Our standardized antenatal class, which was performed in an area with a high rate of cesarean section, significantly reduced this rate, and this was still significant after adjustment for potential confounders.